ИРГЭДИЙН УЛС ТӨРИЙН ҮЗЭЛ СУРТАЛЫН ТАРХАЛТЫГ УЛС ТӨРИЙН ГАЗАРЗҮЙН ҮҮДНЭЭС ТОДОРХОЙЛОХ СУДАЛГАА - Д.Оюунчимэг; Г.Цогтдэлгэр (Politology, 2023)
Peoples political ideology is determined by study of political geography theory and methodology. Therefore, the people’s political ideology is described all over the country and region by the cartography approach. The aim of this research work is to determine the micro environmental situations and impact factors using the hot-spot analysis. In addition, I considered the size of research area as an electoral district and gathered information from 480 respondents. I chose the respondents by cluster collection approach using questionnaire method and considered the level of collection as 99% probability and respondents as ±6 interval. This research is significant to determine the political attitude of the citizens, define the spatial dependence and evaluate the spatial situations of the political parties. I determined the spatial situations by studying the political attitude of the citizens using hot-spot analysis. This research work is the basic study which will be carried out at micro level of Peoples political ideology study.